PERBANDINGAN PENAMPILAN PRODUKSI AYAM BROILER YANG DIPELIHARA PADA KETINGGIAN YANG BERBEDA DI KABUPATEN MOJOKERTO PROVINSI JAWA TIMUR - Samsul Wahyudi; Mubarak Akbar (Universitas Islam Kadiri, 2018)
Mojokerto Regency East Java Province is characterized by a very varied geographical situation ranging from lowland to upland (upland). In general the two regions have different environmental characteristics. Lowland temperature 31-34 oC, has an open expanse, rarely have trees and high buildings, so wind speed is relatively high. High temperature 25-28 oC, lots of forest, low wind speed. The research was conducted in Broiler Chicken Breeders in Mojokerto Regency, East Java Province. Research location at high plateau in District of Trawas and lowland in District of Trowulan. Technical implementation of research conducted by survey technique. The variables of this research are feed consumption, weight gain (PBB), Feed Conversion Ratio (FCR), and mortality. The analysis method to know the difference of broiler chicken production performance which is maintained in highland and lowland is used t-test (SPSS), to know non finasial aspect, it is used descriptive method, while to explain profit and feasibility of laying duck business used net income calculation (π) , R / C, BEP, and Rentability. Management of broiler chicken maintenance in the lowlands is better when compared with the management of broiler chickens on the plateau. The appearance of broiler chicken production maintained in the highlands and lowlands did not differ significantly